REPRESENTASI STEREOTIP ISLAM DALAM ANIME THE JOURNEY - Luthfi Hidayah; Teguh Setyo Budi Utomo (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
The Journey anime with the main character Aws is one of the most popular anime in Indonesia. This anime tells the story of the struggle of Aws, a Meccan youth, in resisting the attack of Abraha's elephant troops who wanted to destroy the Kaaba. This research uses critical discourse analysis by Teun A. van Dijk to analyze the stereotypical representation of Islam in the anime The Journey. Critical discourse analysis is one of the most influential theories of discourse analysis. This theory focuses on how text and discourse can be used to construct and reconstruct reality. The research results show that the anime The Journey represents Islam positively. Aws is described as a brave, tough and big-hearted figure. He represents noble Islamic values, such as courage, justice and peace. However, this research also found several Islamic stereotypes in the anime The Journey. For example, Islam is described as an exclusive religion and intolerant of other religions. Apart from that, Islam is also depicted as a radical and terrorist religion. The problems in this research are: (1) How is the stereotypical representation of Islam in the anime The Journey? (2) How is the discourse surrounding the representation displayed in the anime The Journey seen from the text level (macro structure, micro structure and superstructure? This research uses a qualitative approach with the discourse analysis research method developed by Teun A Van Dijk. To study or describe and To analyze with critical reasoning, a descriptive-analytical approach is used. This type of descriptive research aims to describe the results of research findings systematically, factually and accurately. The definition of descriptive analysis itself is a way of reporting data by explaining, giving a picture, and qualifying and interpreting the data what is collected as it is, after that it is concluded.